2017
DOI: 10.1111/aos.13530
|View full text |Cite
|
Sign up to set email alerts
|

The effects of antioxidants on ocular blood flow in patients with glaucoma

Abstract: One-month oral administration of antioxidants produced increases in biomarkers of ocular blood flow within retinal and retrobulbar vascular beds in patients with OAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 29 publications
1
24
0
2
Order By: Relevance
“…Harris et al. () prospectively studied the effects of antioxidant dietary supplement therapy on ocular blood flow markers including OPP, retrobulbar blood flow and retinal capillary blood flow. After 1 month of antioxidant supplementation, the investigators reported on beneficial increases in these biomarkers compared to control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Harris et al. () prospectively studied the effects of antioxidant dietary supplement therapy on ocular blood flow markers including OPP, retrobulbar blood flow and retinal capillary blood flow. After 1 month of antioxidant supplementation, the investigators reported on beneficial increases in these biomarkers compared to control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exercise is known for its antioxidating ability (Thirupathi & de Souza ), while antioxidants were found to be associated with increase in OBF (Harris et al. ).…”
Section: Physical Exercise and Ocular Perfusionmentioning
confidence: 99%
“…We observe in patients treated a decrease in significant additional of the IOP and an improvement from the PERG amplitude to 6, 9, and 12 months, and sensitivity foveola 12 months Harris et al [55] 45 patients treated, a group with the antioxidant and the other with placebo…”
Section: Ginkgo Biloba Extractmentioning
confidence: 50%